Effectiveness of Teaching Classes about Postpartum Perineum Care in Nurse Midwives Practices in Delivery Rooms at Basra City’s Hospitals - Adnan Jawad, Zahraa; H. Khairi, Suhad (International Journal of Psychosocial Rehabilitation, 2020)
Background: Perineal care help to prevent infection promote healing and provide comfort to the mother and preventing infection of the episiotomy wound, bladder and uterus.Objectives: To find out the effectiveness of teaching classes on nurse midwives about postpartum perineum care.Subject and Method: A quasi-experimental design (pretest and posttest) for (30) nurse/ midwives of nonprobability (purposive) sample who are working in delivery room at two teaching hospitals at Basra city, the sample divided to two groups fifteen nurse /midwives for study group and others for control group. The program conducted through three stages, the first assessing knowledge and practice of the sampling before implementing program, the second stage study group received teaching module on perineal care and in third stage participants completed a questionnaire at posttest Data analyzed by using both descriptive and inferential statistics.Results: The results of study showed that increase in participants’ knowledge for the study group from (32.6) in the pretest to (39.4) in the posttest. Also, there is increase in participants’ practices for the study group from (32.06) in the pretest to (394) in the posttest in the study group.Conclusion: There is a statistically positive significant correlation between participants’ years of experience in the delivery room and their knowledge in the pretest time.